Archaeological Investigations of the Hermitage Expedition on Berezan Island in 2005 - Chistov, Dmitrij (Hyperboreus, 2006)
A survey of the excavations on the Berezan Island (the estuary of Dnepr and S. Bug) conducted by the Hermitage Expedition.